Ink‐Free Reversible Optical Writing in Monolayers by Polymerization of a Trifunctional Monomer: Toward Rewritable "Molecular Paper". Issue 27 (9th May 2017) - Müller, Vivian; Hungerland, Tim; Baljozovic, Milos; Jung, Thomas; Spencer, Nicholas D.; Eghlidi, Hadi; Payamyar, Payam; Schlüter, A. Dieter
Abstract : A Langmuir–Blodgett film consisting of a dense array of trifunctional monomers bearing three 1, 8‐diazaanthracene units is polymerized at an air/water interface or after transfer on solid substrates. The transfer does not affect the excimer fluorescence of the film, indicating that the monomers' packing with their diazaanthracene units stacked face‐to‐face is retained—a prerequisite for successful polymerization. The monomer film can be polymerized in confined areas on solid substrates by UV irradiation with a confocal microscope laser. The underlying chemistry of the polymerization, a [4+4]‐cycloaddition of the diazaanthracene units, leads to disappearance of the fluorescence in the irradiated regions which enables writing into the monolayer on a µm scale—thus the term "molecular paper." The reaction can be reversed by heating which leads to a recovery of the fluorescence and to erasing of the writing. Alternative pathways for this phenomenon are discussed and control experiments are conducted to rule them out. Abstract : "Molecular paper" is nanometer thin, fluorescent film that can be deposited on various substrates and written onto by irradiation with a confocal microscope laser. Irradiation leads to disappearance of the fluorescence in the targeted area, allowing writing on a micrometer scale. This process is reversible by heating which recovers the film's fluorescence and "erases" the writing.